2022
DOI: 10.3389/fneur.2022.886329
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia- and Inflammation-Related Transcription Factor SP3 May Be Involved in Platelet Activation and Inflammation in Intracranial Hemorrhage

Abstract: The purpose of this study was to identify the biomarkers implicated in the development of intracranial hemorrhage (ICH) and potential regulatory pathways. In the transcriptomic data for patients with ICH, we identified DEmiRNAs and DEmRNAs related to hypoxia, inflammation, and their transcription factors (TFs). An ICH-based miRNA-TF-mRNA regulatory network was thus constructed, and four biomarkers (TIMP1, PLAUR, DDIT3, and CD40) were screened for their association with inflammation or hypoxia by machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In addition to the motif activity changes of transcription factors, with the combinatory treated sample, we observed a decrease in the activity of the transcription factor SP1, known to be involved in inflammatory processes. Moreover, SP3, a transcription factor recognized for its anti-inflammatory effects and closely linked to transcription factor SP1 ( 13 ), exhibited an increase, in the same sample, when compared to the TGF-β-treated sample ( Fig. 4F, G ).…”
Section: Resultsmentioning
confidence: 89%
“…In addition to the motif activity changes of transcription factors, with the combinatory treated sample, we observed a decrease in the activity of the transcription factor SP1, known to be involved in inflammatory processes. Moreover, SP3, a transcription factor recognized for its anti-inflammatory effects and closely linked to transcription factor SP1 ( 13 ), exhibited an increase, in the same sample, when compared to the TGF-β-treated sample ( Fig. 4F, G ).…”
Section: Resultsmentioning
confidence: 89%
“…Studies have shown that TIMP1 is related not only to inflammation but also to the indicators of fibrosis. 26 , 27 , 28 , 29 Taken together, the mechanism by which RASSF4 affects fibrosis needs further study.
Figure 7 RASSF4 inhibits lipid synthesis and inflammation in hepatocytes.
…”
Section: Resultsmentioning
confidence: 99%
“…Among the top canonical pathways identified by Ingenuity Pathway Analysis (IPA) were phosphatase and tensin homolog (PTEN) signaling as well as ciliary neurotrophic factor (CNTF) signaling, both of which exert distinct immunomodulatory (including inflammatory) effects [91][92][93] and which have been found to be associated with ADrelated neuropathology [94,95]. Furthermore, among the top master regulators identified by IPA were transcription factor Sp3 and chymase 1, both of which have been implicated in inflammatory regulation [96,97] and are present in higher levels in the brains of AD patients [98,99]. Finally, transforming growth factor beta 1 (TGFB1), which was reduced in the Western cohort, is a pleiotropic cytokine with multifarious effects on both innate and adaptive immune function [100] and has been variously described as pro-and anti-inflammatory [101].…”
Section: Discussionmentioning
confidence: 99%